Dynamic Analysis of the Complex Motion of Three-Section Cudgel in Wushu Sports - Man Xu; Yiran Jiang; Xingfu He; Juntong Yuan; Ying Gao (Applied Sciences, 2021)
Purpose: To provide some suggestions on how to effectively master these movements during training. Methods: The dynamics method and ABAQUS simulation analysis were used to analyze the two technical movements of the three-section cudgels: wrestling cudgels and retrieving cudgels. Results: In the process of wrestling the cudgel, the best effect is achieved when the height of the cudgel holding hand is between 70 cm and 80 cm from the ground. The maximum height of the rebound was very similar with different initial angular velocities, at 4.5–9 cm. The initial angular velocities caused significant impact to the horizontal movement of cudgel at 8 s. By excluding the errors, the horizontal movement of cudgel increased approximately linearly with the increase of the initial angular velocity. Conclusions: When the height between held cudgel and the ground was controlled at 1.5 times the height of the middle section, the rebound of the tail section was the least. When completing the movement of three-section cudgel, the cudgel body should be in the same plane perpendicular to the ground and to better retrieve the three-section cudgel. The main factor affecting the cudgel wrestling was the height between the cudgel holder and the ground.